CORROSION RESISTANCE IMPROVEMENT OF AISI 316L STAINLESS STEEL USING NITROGEN ION IMPLANTATION - Sudjatmoko .; Lely Susita R.M.; Wirjoadi .; Bambang Siswanto (GANENDRA Majalah IPTEK Nuklir, 2013)
The nitrogen ion implantation can be used to improve surface mechanical properties and corrosion resistance behavior of AISI 316L stainless steels by modifying the near-surface layers of these materials. In this study, an AISI 316L stainless steel plate was implanted with the optimum ion dose of 5  1016 ion/cm2 for ion energy variation of 60, 80 and 100 keV. Microhardness was measured by Vickers method, and the results of measurements clearly indicate an enhancement hardness behavior for nitrogen implanted layer. It is found that the implanted layer hardness was increased by a factor of 1.3 in comparison to that of the unimplanted samples. The increased hardness resulting from nitrogen ion implantation was attributed to the formation of an iron nitride phase. Microstructure, chemical composition and surface morphology studied using the technique of Scanning Electron Microscope (SEM) coupled with Energy Dispersive X-ray (EDX) and X-ray Diffraction (XRD). Analysis of SEM-EDX micrographs and XRD diffraction patterns indicate that the nitrogen implanted layer is composed of a metastable single phase which has properties very hard, good corrosion resistance behavior and wear resistance surface layers of stainless steel components. Effects of nitrogen ion implantation on the corrosion properties of AISI 316L stainless steels was evaluated using potentiostat PGS 201T. Corrosion properties of test results showed that there was a significant improvement in the corrosion resistance in the case of nitrogen implanted samples.